Burden of Acute Gastrointestinal Illness in Gálvez, Argentina, 2007 (Journal of Health, Population and Nutrition, 2010)
This study evaluated the magnitude and distribution of acute gastrointestinal illness (GI) in Gálvez, Argentina, and assessed the outcome of a seven-day versus 30-day recall period in survey methodology. A crosssectional population survey, with either a seven-day or a 30-day retrospective recall period, was conducted through door-to-door visits to randomly-selected residents during the 'high' and the 'low' seasons of GI in the community. Comparisons were made between the annual incidence rates obtained using the sevenday and the 30-day recall period. Using the 30-day recall period, the mean annual incidence rates was 0.43 (low season of GI) and 0.49 (high season of GI) episodes per person-year. Using the seven-day recall period, the mean annual incidence rate was 0.76 (low season of GI) and 2.66 (high season of GI) episodes per person-year. This study highlights the significant burden of GI in a South American community and confirms the importance of seasonality when investigating GI in the population. The findings suggest that a longer recall period may underestimate the burden of GI in retrospective population surveys of GI. Key words: Cross-sectional studies; Developing country; Diarrhoea; Foodborne diseases; Morbidity; Population surveys; Recall bias; Waterborne diseases; Argentina DOI: 10.3329/jhpn.v28i2.4885 J Health Popul Nutr 2010 Apr; 28(2): 149-158